Long-term prognostic effect of coronary atherosclerotic burden validation of the computed tomography-leaman score - Mushtaq, Saima (2015)
Background: Computed tomography-adapted Leaman score (CT-LeSc) was developed to quantify coronary CT angiography information about atherosclerotic burden (lesion localization, stenosis degree, and plaque composition). The objective of the study is to evaluate CT-LeSc long-term prognostic value in patients with suspected coronary artery disease (CAD). Methods and Results: Single-center prospective registry including 1304 consecutive patients undergoing coronary CT angiography for suspected CAD. High CT-LeSc was defined by upper tertile (score, >5) cutoff. Segment involvement score and segment stenosis score were also evaluated. Hard cardiac events (cardiac death and nonfatal acute coronary syndromes) were considered for analysis. Different Cox regression models were used to identify independent event predictors. Kaplan-Meier event-free survival was evaluated in 4 patient subgroups stratified by obstructive (≥50% stenosis) versus nonobstructive CAD and a high (>5) versus a low (≤5) CT-LeSc. Of 1196 patients included in the final analysis (mean follow-up of 52±22 months), 125 patients experienced 136 hard events (18 cardiac deaths and 118 nonfatal myocardial infarction). All atherosclerotic burden scores were independent predictors of cardiac events (hazard ratios of 3.09 for segment involvement score, 4.42 for segment stenosis score, and 5.39 for CT-LeSc). Cumulative eventfree survival was 76.8% with a high CT-LeSc and 96.0% with a low CT-LeSc. Event-free survival in nonobstructive CAD with high CT-LeSc (78.6%) was similar to obstructive CAD with high CT-LeSc (76.5%) but lower than obstructive CAD with low CT-LeSc (80.7%). Conclusions: CT-LeSc is an independent long-term predictor of hard cardiac events. Patients with nonobstructive CAD and high CT-LeSc had hard event-free survival similar to patients with obstructive CAD.